2015
DOI: 10.1177/2156587215573141
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Using Herbal Medicines Among Patients With Hypertension in Kerman, Iran, 2012-2013

Abstract: Introduction. The use of medicinal plants has dramatically increased in recent years. Given the increasing rate of hypertension and medical plants usage by these patients and considering drug interactions due to concomitant use with drugs, the present study aims to evaluate the rate of medicinal plants usage in hypertensive patients. Methods. This is a cross-sectional study (descriptive-analytical) in which 650 hypertensive patients referring to the subspecialty clinic of Kerman were questioned about medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“… 5 , 19 , 24 Tajadini showed that herbal medicines were used as adjunctive therapy for lowering blood pressure. 14 Meanwhile, approximately 8–70.4% of patients claimed that herbal medicines were highly effective and did not cause problems when used concurrently with antihypertensive drugs. 20–22 This result was similar to that of the study of Delgoda et al that showed that the reason for the concurrent use of herbal medicines and prescribed drugs was attributed to hereditary beliefs.…”
Section: Factors Correlated With the Simultaneous Use Of Herbal Medicmentioning
confidence: 99%
“… 5 , 19 , 24 Tajadini showed that herbal medicines were used as adjunctive therapy for lowering blood pressure. 14 Meanwhile, approximately 8–70.4% of patients claimed that herbal medicines were highly effective and did not cause problems when used concurrently with antihypertensive drugs. 20–22 This result was similar to that of the study of Delgoda et al that showed that the reason for the concurrent use of herbal medicines and prescribed drugs was attributed to hereditary beliefs.…”
Section: Factors Correlated With the Simultaneous Use Of Herbal Medicmentioning
confidence: 99%
“…In this study, the prevalence of crude herbs use is 30.6%-double the prevalence of herbal medicine usage in a previous study conducted in an urban primary health clinic in Malaysia [11]. Other previous studies conducted in the Asian countries reported varying prevalence: Palestine (62.1%) [14], China (18.5%) [28], and Iran (29.4%) [29]. The different prevalence noted could be attributed to these factors: availability and diversity of herbs species across countries with different climate; varied cultural practices of people with different ethnicities; and different definitions of herbs used in the previous studies.…”
Section: Discussionmentioning
confidence: 52%
“…From this study, some of the more prominently used crude herbs by patients are Centella asiatica, Momordica charantia, Carica papaya, Cucumis sativus, Parkia speciosa, Moringa oleifera and Cosmos caudatus. In two previous surveys performed locally, Momordica charantia, Centella asiatica and Carica papaya are similar to some of the main herbs used by patients with hypertension [11,29]. This common finding could be due to the availability of and accessibility to these herbs in the tropical climate of Malaysia.…”
Section: Plos Onementioning
confidence: 73%
“…Scientific methods of infertility treatment have advanced in recent years but they are mostly expensive, invasive, and time-consuming. 2 Complementary medicine is becoming more and more popular in the world, especially Western countries 3 , 4 ; for example, 75% of the women in the reproductive age used one of the methods of complementary medicine in 2006. 5 …”
Section: Discussionmentioning
confidence: 99%